FRI0141 Prevalence of thyroid disease in systemic lupus erythematosus and primary sjÖgren syndrome. (1st June 2001) - Alexandre, M; Braña, A; Barcelos, A; Salvador, MJ; Silva, C; Inês, L; Nour, D; Reis, P; Silva, JA Pereira da; Malcata, A; Porto, A
Abstract : Background: Thyroid dysfunction (hypo and hypertiroidism) has been described among patients with connective tissue diseases, particularly in patients with systemic lupus erythematosus (SLE) and primary Sjögren syndrome (PSS). Also a high prevalence of anti-thyroid antibodies (ATA) has been found in these patients. Objectives: To study:1) Thyroid function and morphology in a population of SLE and PSS patients; 2) To evaluate the prevalence of ATA in these patients; 3) To correlate clinical manifestations with laboratory data. Methods: We studied serum levels of thyroid hormones, TSH, anti-thyroglobulin and anti-microssomal antibodies in 70 consecutive patients (50 with SLE and 20 with PSS), followed in our department. We performed thyroid ultrasound in all patients. Patients were asked about signs and symptoms related to the manifestations of thyroid dysfunction. Results: Conclusion: In this group of patients we found a high prevalence of thyroid morphology abnormalities and thyroid dysfunction. In both groups less than half of the patients with thyroid dysfunction presented related symptoms. These results suggest that all SLE and PSS patients should be routinely screened for thyroid disease even in the absence of clinical manifestations.